2016
DOI: 10.1016/j.cub.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised statistical learning in newly hatched chicks

Abstract: The ability to extract probabilistic information from visual inputs has been reported in human adults and infants (reviewed in [1,2]), and in adults of non-human species, though only under supervised (conditioning) procedures [3]. Here, we report spontaneous sensitivity to the probabilistic structure underlying sequences of visual stimuli in newly hatched domestic chicks using filial imprinting, suggesting that statistical learning may be fully operating at the onset of life in precocial avian species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 8 publications
8
57
2
Order By: Relevance
“…We have also tried to highlight the ways in which statistical learning abilities serve infants well, given the structure of the environment into which they are born. At least some of these abilities are observed in other species (e.g., Abe & Watanabe 2011, Santolin et al 2016, Toro & Trobalón 2005). Almost 50 years ago, Rescorla (1968) demonstrated that conditioning is actually dependent on more complicated factors than just contiguity of the pairing.…”
Section: Why Are We Statistical Learners?mentioning
confidence: 91%
“…We have also tried to highlight the ways in which statistical learning abilities serve infants well, given the structure of the environment into which they are born. At least some of these abilities are observed in other species (e.g., Abe & Watanabe 2011, Santolin et al 2016, Toro & Trobalón 2005). Almost 50 years ago, Rescorla (1968) demonstrated that conditioning is actually dependent on more complicated factors than just contiguity of the pairing.…”
Section: Why Are We Statistical Learners?mentioning
confidence: 91%
“…This can be done by recognizing the frequency with which groups of sounds occur in a given order, an ability shown by human infants and adults [ 9 , 10 , 11 , 12 ]. However, this ability is not restricted to linguistic or even auditory input [ 13 , 14 , 15 ] and is shown also by nonhuman animals [ 3 , 16 , 17 , 18 , 19 , 20 ]. Likewise, other abilities necessary to the evolution and acquisition of linguistic syntax, investigated by studies that test humans’ and animals’ capability to recognize various kinds of regularities in the temporal order of a sequence of elements [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], are not restricted to language [ 28 , 29 , 30 ] or to humans [ 23 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this brief tracking shot of biological predispositions, I have shown that imprinting is still instrumental in the study of aspects of chicks' cognition that are relevant to human cognition. Imprinting applies successfully to the investigation of perception, agent recognition, physical reasoning, and spatial reorientation (reviews in Vallortigara & Chiandetti, 2017), but also of numerical cognition (review in Vallortigara, 2017) and other forms of abstract learning (see, e.g., Santolin, Rosa-Salva, Vallortigara, & Regolin, 2016). Addressing of issues such as whether basic mechanisms in core domains of cognition are inborn is only possible in suitable animal models.…”
Section: Discussionmentioning
confidence: 99%